Challenges in the logistical management of a cookie manufacturing microenterprise from the perspective of primary and support activities integration (Research, Society and Development, 2020)
Since origin to consumption, logistics management accompanies the delivery of goods and services in order to meet customer needs. However, an inefficient integration and coordination of logistics activities can contribute to the negative profitability of the enterprise. The central element of this article was to identify what are the main challenges in the logistical management of integrating primary and support activities in a cookie manufacturing microenterprise. The study is justified due to the accelerated expansion that contributed to the non-effective planning of the logistics sector, as well as the decrease in the company's performance towards customers. In this context, we sought to develop research of an applied nature, qualitative approach and exploratory objective. The technical procedure used was the case study. The research consisted of (i) defining a conceptual-theoretical structure; (ii) plan the case; (iii) conduct the pilot test; (iv) collect the data; (v) analyse the data; and (vi) generate the report. Multiple challenges were noted during the analysis, such as delays in delivering goods to customers. It is suggested to hire a logistics operator at the cookie factory to assist in the creation, planning, implementation, development and management of transport activities, inventory maintenance and order processing. The final conclusions of the study show that the presence of the logistics operator may generate several benefits, such as increase in the quality of service offered to the customer and obtaining competitive advantage over the competition.